The Impact of Technology Readiness on Mobile Cloud Computing Technology Acceptance among College Student in Indonesia - Pradana, Gregorius Adhisakti; Suharto, Yulianto (Journal of Business and Management, 2020)
Abstract. Adopting mobile cloud computing (MCC) is expected to be one of the superior approaches to improving college student’s performance. Many students may use the functions for far fewer tasks than the MCC supports. This may depend on the technological personality associated with the acceptance of MCC. The purpose of this research is to investigate students’ personality traits in regard to technology readiness toward MCC acceptance. The author use Technology Readiness and Acceptance Model (TRAM). The study used an online questionnaire to collect 400 valid responses from active students from universities in Indonesia. Path Analysis was utilized to analyze the collected data. The findings indicate that Indonesian college students are optimistic, innovative, comfortable, but technology insecure. Optimism and Innovativeness are the driving force behind the adoption of technology, and Insecurity is an obstacle of technology adoption for them. The major findings of this study also reveal that four personality traits of technology readiness have different effects on perceived usefulness and perceived ease of use about MCC. This research proves that personality influences the adoption of technology. This research suggest universities and other student’s organizations must be aware of this relationship when initiating the implementation of technology.Keywords: Mobile Cloud Computing (MCC), Indonesian College Student, Technology Readiness (TR), Technology Acceptance Model (TAM), Technology Readiness and Acceptance Model (TRAM).